Asuhan Keperawatan Pada An.N Dengan Diagnosa Medis Gastroentritis Akut (Gea) - Dian Budiati; Nonok Karlina; Yulianingsih; Umi Najihah (Awatara Publisher, 2024)
Acute gastroenteritis is a disease caused by viral, bacterial, or parasitic infections affecting the gastrointestinal tract. Its main symptoms are diarrhea and/or vomiting. Cases of acute gastroenteritis should be managed comprehensively to prevent dehydration and maintain the patient's fluid and electrolyte balance. The objective of this study is to understand nursing care for children diagnosed with acute gastroenteritis. The research method used is a case study. The subject of the study is Child N, diagnosed with acute gastroenteritis. The research was conducted in the Anyelir Ward at Waled Regional Hospital in Cirebon. The nursing intervention for the child with acute gastroenteritis included fluid and electrolyte administration for three days. Evaluation showed that the problem was resolved, and the family was advised to continue providing oral fluids to maintain fluid balance in the body.